2015
DOI: 10.2174/1874110x01509012565
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Hybrid Algorithm Based on PSO and BP for Stock Price Forecasting

Abstract: Stock price prediction is the main concern for financial firms and private investors. In this paper, we proposed a hybrid BP neural network combining adaptive PSO algorithm (HBP-PSO) to predict the stock price. HBP-PSO takes full use of the global searching capability of PSO and the local searching advantages of BP Neural Network. The PSO algorithm is applied for training the connection weights and thresholds of BP, in order to take advantage of BP, each particle in PSO swarm will be optimized by error correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…They proposed a hybrid BP neural network combining adaptive particle swarm optimization algorithm (HBP-PSO) to predict the stock price of "Zhong Guo Yi Yao" (600056). The results support that the trend prediction accuracy of HBP-PSO is better than that of the simple neural network [6]. Using this criterion can ensure the prediction accuracy of the up and down signals of stock price to reduce the possibility of trading errors.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…They proposed a hybrid BP neural network combining adaptive particle swarm optimization algorithm (HBP-PSO) to predict the stock price of "Zhong Guo Yi Yao" (600056). The results support that the trend prediction accuracy of HBP-PSO is better than that of the simple neural network [6]. Using this criterion can ensure the prediction accuracy of the up and down signals of stock price to reduce the possibility of trading errors.…”
Section: Introductionsupporting
confidence: 61%
“…However, the second way does not yet work very well. One important reason is that different periods of a stock market, for example, rising period and falling period, have different inherent laws and scholars usually use a single neural networks model and the same set of parameters to deal with the different periods [5,6]. Another reason, the most difficult problem, is the effect of unexpected news, which could hardly be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…For the prediction, an update state method has been exploited to forecast time stages one after another and renovate the network state at every forecast. Furthermore, to prove the significance of the proposed model, the model is applied to three different datasets and benchmarked with three popular stock price forecasting methods Sun's model [21], Roondiwala's model [22], Basak's model [23]. Dataset #I is elected from the Standard and Poor's 500 Index; dataset #II comes from China Min-sheng Bank (CMSB), and dataset #III comes from Dow Jones Industrial Average [17].…”
Section: Experiments and Comparisonsmentioning
confidence: 99%
“…Although trading on the foreign exchange instead of the stock exchange, the authors note that their system has shown to be profitable in testing. Sun and Gao [20] used PSO to optimize the weights on a neural network that predicted the prices of securities on an exchange. The authors note that their system was able to predict the price with an error rate of around 30% when compared to the actual prices.…”
Section: Market Timingmentioning
confidence: 99%